Village Budget Management Apbdes in Increasing Transparency and Accountability of Village Fund Use: a Case Study in Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency - Faijah Maya Sari Siregar; Irawan Irawan; Ayu Kurnia Sari (Journal of Research in Social Science and Humanities, 2025)
This study analyzes the management of the Village Revenue and Expenditure Budget (APBDes) in improving transparency and accountability in the use of Village Funds in Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency for the 2020–2024 period. The research method uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation in the form of reports on the realization of the 2020–2024 APBDes and related regulations, with informants determined purposively including village officials and the community. The results of the study indicate that the administrative management of the APBDes has been running according to the stages of planning, implementation, administration, reporting, and accountability as stipulated in Regulation of the Minister of Home Affairs Number 20 of 2018, with relatively consistent budget realization. However, public transparency and community participation are not optimal, marked by limited access to APBDes information and low community involvement in village deliberations. This finding confirms the gap between procedural compliance and public information disclosure. Therefore, strengthening the dissemination of more detailed information and increasing public participation is necessary to strengthen substantive accountability and the application of good governance principles in the management of the Village Budget